Infiltrating spinal cord astrocytomas: Epidemiology, diagnosis, treatments and future directions. (July 2016) - Abd-El-Barr, Muhammad M.; Huang, Kevin T.; Chi, John H.
Highlights: Infiltrating spinal cord astrocytomas are particularly challenging to treat. Surgical treatment consists of biopsy with maximal safe resection if possible. A multidisciplinary effort is needed to make progress against this formidable tumor. Abstract: Spinal cord gliomas, consisting mostly of ependymomas and astrocytomas, are rare entities. Of the gliomas, infiltrating astrocytomas are particularly challenging entities to treat due to their invasive nature. Surgical resection is oftentimes not possible without subjecting patients to permanent neurological deficits because of the difficulty in establishing clear tissue planes. As more is learned about the molecular genetics, genomics, and biology of these tumors, it is becoming more apparent that there are important differences between these tumors and their more common intracranial counterparts. There also appears to be important clinical differences between low-grade and high-grade astrocytomas. A multidisciplinary approach is needed to optimize the treatment of these difficult tumors.